2013
DOI: 10.1039/c3tb20649a
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and transfection activity of DNA complexes based on poly(ethylene glycol)-poly(l-glutamine) copolymer with PAMAM G2

Abstract: Poly(ethylene glycol)-poly(L-glutamine) (PEG-PLGA) copolymer EA-G2 (or EA-G1) was prepared by aminolysis of poly(ethylene glycol)-poly(L-benzyl glutamate) (PEG-PBLG) using PAMAM G2 (or G1). The chemical structure of PEG-PLGA was confirmed by FT-IR, 1 H-NMR, DSC and GPC. The performances of the EA-G2 (or EA-G1) were assayed by enzyme degradation, MTT method and agarose gel electrophoresis. The particle size, zeta potential and morphology of EA-G2 (or EA-G1)/pDNA complexes were inspected by DLS and AFM. The cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Interestingly, the transfection efficiency of PAE MTN was unexpectedly enhanced by adding chlorpromazine, a clathrin-mediated endocytosis inhibitor. Blocking the clathrin-mediated endocytosis pathway might increase the probability of transporting PAE MTN through caveolea-mediated endocytosis and macropinocytosis pathways 45, 46 and leads to enhanced transfection efficiency. Enhancement of cell internalization of PAE MTN due to the magnetic field was also visualized using TOTO3-labeled DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the transfection efficiency of PAE MTN was unexpectedly enhanced by adding chlorpromazine, a clathrin-mediated endocytosis inhibitor. Blocking the clathrin-mediated endocytosis pathway might increase the probability of transporting PAE MTN through caveolea-mediated endocytosis and macropinocytosis pathways 45, 46 and leads to enhanced transfection efficiency. Enhancement of cell internalization of PAE MTN due to the magnetic field was also visualized using TOTO3-labeled DNA.…”
Section: Resultsmentioning
confidence: 99%
“…120 Recently, Sarkar et al, 121 conjugated N -maleyl chitosan (NMCTS) by Michael type addition reaction to improve solubility, transfection efficiency and low the toxicity (Table III). Pan et al 122 reported as well high transfection activity with moderate toxicity of a copolymer made of poly(ethylene glycol)-poly-(L-glutamine) mixed with high molecular weight PAMAMs (Table III).…”
Section: Cytotoxicity Of Polyplexesmentioning
confidence: 98%
“…Feng and co‐workers have examined the transfection efficacy and cellular uptake of a PEG‐PGA copolypeptide grafted to two generations of PAMAM dendrimer . Using conventional ROP techniques, the polypeptide was prepared via PEG‐NH 2 initiation of the BLG NCA monomer.…”
Section: Star Polypeptides For Delivery Of Therapeuticsmentioning
confidence: 99%